Lung recruitment strategy and surfactant in delivery room - Gargano, G.; Braibanti, S. (Acta Biomedica Atenei Parmensis, 2014)
The aim of neonatal resuscitation is to establish an effective ventilation, avoiding lung damage. PEEP and T-piece use, as well as Sustained Lung Inflation, lower O2 target and appropriately timed surfactant administration analyzed. A new “gentle” respiratory approach in delivery room can improve newborn respiratory outcome.